Central and Eastern Europe : New Member States (NMS) Policy Forum, 2014, Staff Report on Cluster Consultations-Common Policy Frameworks and Challenges. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES 2014 marked the tenth anniversary of accession to the EU of the first group of Central and Eastern European (CEE) countries. The first NMS Policy Forum was launched in the fall of 2014 as a platform for discussing policy frameworks and issues relevant for non-euro area NMS. It brought together representatives of the six CEE countries that are EU members but are not yet in the euro area - Bulgaria, Croatia, Czech Republic, Hungary, Poland, and Romania (NMS-6), as well as the ECB, the European Commission and the IMF. Discussions focused on four themes: Euro adoption: A once sizeable country risk premium associated with joining the euro area has mostly vanished, as the euro crisis has exposed flaws in the euro area's institutional framework. Further, the crisis has illustrated both risks and benefits from adoption: monetary autonomy has proven helpful for absorbing shocks, while foreign currency mismatches-that can be much reduced with euro adoption-have shown to be a key vulnerability. Flexible labor markets, fiscal and macro-prudential policy space, and income convergence are prerequisites for successful adoption. Opting into the Banking Union (BU) before euro adoption: The lack of equal (or fully equivalent) treatment of the BU members and non-euro area opt-ins-regarding their role in the Single Supervisory Mechanism (SSM), as well as access to common liquidity and fiscal backstops-makes opting into the BU before euro adoption less attractive. Countries that would benefit most from early opt-in are those that see the BU as a way to enhance the quality and credibility of bank supervision or to gain access to larger industry-funded common backstops. The EU's fiscal framework and pension reform: In the wake of the crisis, many NMS abolished second pillar pension funds. Further reforms to the EU's fiscal framework are warranted to remove disincentives for setting up and maintaining second pension pillars and, more generally, for structural reforms. Making the most of the EU single market and EU Services Directive: Structural reforms to strengthen human capital, skills match, labor market efficiency, and foreign investment environment will help NMS to reap full benefits from EU integration. Further liberalization of trade in services will likely benefit the NMS-6 more than other EU members.